c-MRI findings after crystal meth abuse - Möbius, Cornelia; Kustermann, Andreas; Struffert, Tobias; Kornhuber, Johannes; Mueller, Helge H. (Journal of Addiction Medicine, 2014)
We describe a case of intoxication with N-methylamphetamine (Crystal-METH) after withdrawal. Crystal-METH abuse was associated with persisting neurological symptoms and impressive structural white matter alterations. Magnetic resonance imaging should be recommended to document the possible extensive changes in amphetamine abuse, which increases dramatically.
EVALuna2:22312